Perbedaan Hasil Belajar Materi Bangun Ruang Sisi Datar Siswa yang Menggunakan Model Problem Based Learning dengan Model Direct Instruction di SMP Negeri 2 Langowan - Stevanli Tatia; James U. L. Mangobi; Ontang Manurung (Departement of Mathematics Education, 2023)
This research aims to determine the differences in student learning outcomes in the material Building Flat Side Spaces using the Problem Based Learning model and the direct instruction model, in this case the differences in student learning outcomes are seen from the average value. The type of research used is comparative with a quasi-experimental method (quasi experiment), and the research design used is Posttest Only Control Design. This research was carried out at SMP Negeri 2 Langowan. The research subjects were 26 students in class VIII B as the experimental class who were given the Problem Based Teaching model treatment and 26 students in class VIII C as the control class who were given the Direct Instruction model treatment. The average posttest result for the experimental class was 84.73 while for the control class it was 70.07. The results of hypothesis testing using the t-test concluded that the average learning outcomes of students taught using the Problem Based Learning model were more than the average learning outcomes of students taught using the Direct Instruction model.